Effect of Specimen Dimensions on Yield Shear Stress in Torsion Testing of AISI 1020 Steel by Using GRA - Patil, Rajkumar D.; Gore, P. N.; Balwan, Vishal R. (Asian Review of Mechanical Engineering, 2019)
This current research work aims at studying the influence of hollow specimen dimensions such as inner diameter, useful length, outer diameter and fillet radius on yield shear stress of mild steel (AISI 1020) in torsion testing. L9 orthogonal array was selected for design of experiments. Three output parameters of torsion testing such as modulus of rigidity, yield shear stress and ultimate shear stress were calculated by using Nadai method. Single objective optimization was done by using Taguchi method. Further effort was made to simultaneously optimize the specimen dimensions using grey relational analysis (GRA). The yield shear stress was found maximum for the specimen dimensions with outer diameter of 12 mm, inner diameter 3.8 mm, useful length 16.0 mm, and fillet radius 2.0 mm. The confirmation test was also carried out to check the GRA results.